Disparitas Putusan Pengadilan tentang Permohonan Pailit dan PKPU oleh Kreditur terhadap BUMN (Persero) - Dinda Ayu Narassati; Yonathan Aji Pamungkas; Anita Afriana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Based on various collected court decisions, this research aims to highlight the fact that there is a disparity in the view of courts in deciding bankruptcy and debt payment suspension petitions against state-owned enterprises (Persero) by creditors. In addition, this research also explores the original intent of the legislator in Article 2 paragraph (5) juncto Article 223 of Law Nomor 37 of 2004 regarding Bankruptcy and Debt Payment Suspension so that it can be used as an academic reference in breaking the chain of debate because of interpretation differences in judicial practice. The discussion of problems in this research is based on a normative juridical approach, in which the materials and data collected are based on primary and secondary sources. Although the theme raised in this research has been presented in various studies, this research is still based on novelties. This research uses historical interpretation to explore the original intent of the Indonesian Bankruptcy Law legislator. The spotlight on disparities in court views is based on numerous court decisions, so it is sufficient to be used as a basis for the conclusion that disparities exist in practice. Based on historical interpretation according to minutes of the law formation, the legislator's original intent was to limit the bankruptcy and debt payment suspension petitions to state-owned enterprises (Perum), which the finance minister can only submit. Therefore, this provision does not apply to state-owned enterprises (Persero), so the petition against it does not have to be submitted by the finance minister. Meanwhile, there is a disparity in the court's view of judicial practice. Hence, a specific law is needed to reaffirm which party has the authority to submit the petition to a Persero to end the disparity.